Development of 'NumBiz Kidz' Mobile Game Based on MSME Context of Tembokrejo Broiler Chicken to Enhance Early Childhood Numeracy Literacy - Mufidatul Ilmiyah; Rani Darmayanti; Maulid Datul Hasanah; Paulo Vitor da Silva Santiago; Kalim Ullah (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
Numeracy literacy is a fundamental skill for early childhood to understand basic quantitative concepts relevant to daily life, including simple entrepreneurial contexts that foster an entrepreneurial mindset from an early age. However, conventional learning methods often fail to connect abstract mathematical concepts with practical, engaging applications, necessitating the development of innovative learning media. This study aims to conduct the initial development stage of an educational mobile game called "NumBiz Kidz" based on simple entrepreneurship contexts to enhance early childhood numeracy literacy, with a primary focus on the Define stage (Needs Analysis) of the 4D development model (Define, Design, Develop, Disseminate). The research employed a Research and Development (R&D) design using the 4D model, limited to the Define stage. Data collection techniques included observation, in-depth interviews with early childhood teachers and education experts, and document review of curricula, social arithmetic materials, and entrepreneurship case studies from broiler chicken MSMEs in Tembokrejo, Pasuruan. Instruments included observation sheets, semi-structured interview guidelines, and a document review matrix. Data were analyzed using descriptive qualitative methods following Miles and Huberman's interactive model. The findings from the Define stage revealed high urgency for technology-based learning media (mobile games) that explicitly integrate basic numeracy literacy with simple entrepreneurship concepts (e.g., buying and selling, profit, loss) that are contextual and appropriate for early childhood characteristics. Learner analysis indicated that children preferred bright colors (40%), cute characters (35%), and instant rewards (25%). Task analysis produced a simplification matrix that transformed real business concepts (e.g., strategic profit optimization, cost of goods sold calculation, change calculation) into game missions that teach addition, subtraction, quantity comparison, and duration concepts. The final output is a Product Specification Blueprint including functional requirements (simple store, inventory, change calculator, coin leaderboard) and non-functional requirements (Android/iOS platform, 2D animation, inclusive characters).